Induction heating of rotating nonmagnetic billet in magnetic field produced by high-parameter permanent magnets - Doležel, I.; Karban, P.; Mach, F. (Електротехніка і електромеханіка, 2014)
An advanced way of induction heating of nonmagnetic billets is discussed and modeled. The billet rotates in a stationary magnetic
field produced by unmoving high-parameter permanent magnets fixed on magnetic circuit of an appropriate shape. The mathematical model of the problem consisting of two coupled partial differential equations is solved numerically, in the monolithic formulation. Computations are carried out using our own code Agros2D based on a fully adaptive higher-order finite element method. The most important results are verified experimentally on our own laboratory device. Обсуждается и моделируется прогрессивный метод индукционного нагрева немагнитных заготовок. Заготовка вращается в стационарном магнитном поле, создаваемом неподвижными высококоэрцитивными постоянными магнитами, закрепленными на магнитопроводе соответствующей формы. Математическая модель задачи, состоящая из
двух связанных дифференциальных уравнений в частных производных, решается численно в "жесткой" постановке.
Вычисления выполняются с использованием собственного программного обеспечения Agros2D на основе полностью
адаптивного метода конечных элементов высоких порядков. Наиболее важные результаты подтверждены экспериментально на собственном лабораторном оборудовании.